Análise das estruturas municipais de gestão ambiental: o caso dos municípios margeados pelo rio Iguaçu, em seu médio curso Paraná/Brasil. - Bergamim, Juliane Stenzinger (2012)
For many years men have been using nature to promote their livelihoods. However, until recently, this same nature was seen as an inexhaustible source of resources, which could be an appropriation without limits. In Brazil, urban and rural municipalities have always been occupied according economic development or facilities of access and movement. Therefore, the occupation of Permanent Preservation Areas is a reflection of the colonization process in our country. This process of occupation, for many years, has occurred daily by municipalities without being given due importance. In this way, as a result of this process, lots of environmental changes have occurred over the years. Nevertheless, even with greater environmental awareness nowadays, added with a tightening of legislation, the devastation and occupation of protected areas continues to occur. Thus, knowing the importance of preserving these areas, the Federal Constitution of 1988 established in its Article 23 that is common responsibility of the Union, States, Federal District and Municipalities to protect the environment. Beyond that, the Resolution 237/97 of the National Environment Council increases the municipality responsibility in the environmental management process. This way, the work in question aims to analyze the environmental management in municipalities bordered by Iguaçu river, in its Middle Basin. For that, this study took into account the deductive method, the literature search and systematic approach. From the analyzes we found that even belonging to the same region, the municipalities have different characteristics and structure of Environmental Management. These features range from the structure of public administration focused on the process of Environmental Management to the participation of civil society organizations in actions related to the environment. Another finding was that only four (4) of the twelve (12) municipalities have an adequate structure of Environmental Management according to the National System of Environment criteria. This result was mainly due to lack of investment and skilled professionals able to manage the municipal environment. Finally, when compared to the situation of Permanent Preservation Areas in the cities, as indicative of the effectiveness of conservation policies, it was found that the structure of the municipal environmental agencies does not always reflect the protected areas, in other words, the presentation of an appropriate structure of Environmental Management is not the guarantee of a better preservation of the environment for municipalities surveyed. This finding occurred because none of the twelve (12) municipalities fulfill what determines the Federal Law. Based on these results it is evident the need for greater investment by the public government and also greater participation of civil society, that is, more specific actions that will really reflect the effectiveness of environmental conservation policies, ensuring, this way, a healthy and quality life for the population.